The influence of emotional intelligence in stress, emotional dissonance and performance of flight attendants - Piñar Chelso, María José; Fernández Castro, Jordi (Anales de Psicología / Annals of Psychology, 2010)
The aim of work was to design a procedure which allows to simulate, with realism, potentially stressful, frequent and real situations with passengers and analyse the role of emotional intelligence in perceived stress, emotional dissonance, perceived difficulty and performance of flight attendants in the face of disruptive passengers. Every one of the participants, 18 flight attendants, by a role-play, interacted with 2 actors, a man and a woman, acted as passengers, in four scenarios (2 situations, a passenger who has placed his suitcase next to one of the emergency exits and a passenger who has been smoking in the toilette and two types of passenger x 2 types of conflictive passengers, category type I or category type II according to the classification carried out by Federal Aviation Administration). The procedure simulated situations potentially stressful, what have been performed with realism and the conflictive situations caused more perceived stress, emotional dissonance and perceived difficulty. The component clarity of TMMS-24 had positive relationships with perceived stress, emotional dissonance and perceived difficulty and negative relationships with performance, measured by non verbal communication.